Extended-spectrum β-lactamases and their clinical importance in community-acquired infections [Toplum kökenli i̇nfeksiyonlarda genişlemiş spektrumlu β-laktamazlar ve klinik önemi] - TİGEN, ELİF; DURMUŞOĞLU, LÜTFİYE (AVES Ibrahim Kara, 2012)
Community-acquired extended-spectrum β-lactamase (ESBL) producing organisms cause life threatening infections, the majority of which are urinary tract infections and bacteremias caused by CTX-M enzyme producing Escherichia coli. Approach to these infections requires great care because their mortality rates are high unless timely and appropriate treatment is started.
Keywords: Community-acquired infections; Escherichia coli; β-lactamases